Review on iron availability in soil: interaction of Fe minerals, plants, and microbes - Colombo, Claudio; Palumbo, Giuseppe; He, Ji-Zheng; Pinton, Roberto; Cesco, Stefano (Journal of soils and sediments, 2014)
PURPOSE: The rationale of this paper is to review the state of the art regarding the biotic and abiotic reactions that can influence Fe availability in soils. In soil, the management-induced change from oxic to anoxic environment results in temporal and spatial variations of redox reactions, which, in turn, affect the Fe dynamics and Fe mineral constituents. Measuring the Fe forms in organic complexes and the interaction between bacteria and Fe is a major challenge in getting a better quantitative understanding of the dynamics of Fe in complex soil ecosystems. MATERIALS AND METHODS: We review the existing literature on chemical and biochemical processes in soils related with the availability of Fe that influences plant nutrition. We describe Fe acquisition by plant and bacteria, and the different Fe–organic complexes in order to understand their relationships and the role of Fe in the soil carbon cycle. RESULTS AND DISCUSSION: Although total Fe is generally high in soil, the magnitude of its available fraction is generally very low and is governed by very low solubility of Fe oxides. Plants and microorganisms can have different strategies in order to improve Fe uptake including the release of organic molecules and metabolites able to form complexes with Feᴵᴵᴵ. Microorganisms appear to be highly competitive for Fe compared with plant roots. Crystalline Fe and poorly crystalline (hydro)oxides are also able to influence the carbon storage in soil. CONCLUSION: The solubility of crystalline Fe minerals in soil is usually very low; however, the interaction with plant, microbes, and organic substance can improve the formation of soluble Feᴵᴵᴵ complexes and increase the availability of Fe for plant growth. Microbes release siderophores and plant exudates (e.g., phytosiderophores, organic acids, and flavonoids), which can bind and solubilize the Fe present in minerals. The improved understanding of this topic can enable the identification of effective solutions for remedying Fe deficiency or, alternatively, restricting the onset of its symptoms and yield’s limitations in crops. Therefore, development and testing of new analytical techniques and an integrated approach between soil biology and soil chemistry are important prerequisites.